Enhancing Collaboration Between Radiologists And Nurses: A Pathway To Improved Patient Care (Journal of Namibian Studies : History Politics Culture, 2023)
Collaboration between radiologists and nurses is integral to delivering comprehensive and high-quality patient care in modern healthcare settings. While both professions bring unique expertise to the table, effective teamwork between radiologists and nurses is often hindered by communication barriers, hierarchical structures, and time constraints. This article explores the importance of collaboration between radiologists and nurses and presents strategies for enhancing teamwork in healthcare settings. These strategies include inter-professional education, clear communication channels, team-based care models, and fostering mutual respect and recognition. By overcoming these challenges and promoting collaboration, healthcare institutions can improve patient outcomes, enhance job satisfaction, and ultimately provide more patient-centered care.